Factors affecting wives' role structure in urban family purchase decision making - Md. Sidin, Samsinar; Zawawi, Dahlia; Teo, Boon How (Universiti Putra Malaysia Press, 2013)
Family decision making is a process where families make decisions regarding purchases of goods and services to be consumed by members of the family. Past research indicates that decision making process varies with products and services purchased. Factors found to effect the decision making process include culture, sex role orientation, and resources of husbands and wives. The objectives of this research are to investigate the decision making process and the factors affecting this particular process. Two hundred and fifty-one wives residing in the Klang Valley, Malaysia, were interviewed. Findings indicate that majority of purchases by families are made jointly. Husbands are more dominant in the purchase outcome stage of the decision making process. Language spoken at home is a relatively important cultural element affecting purchase decisions in the family, and sex role orientation seems to influence the purchase of high involvement products. However, wives’ resources do not influence purchase decisions.